2016
DOI: 10.4172/2157-7110.1000573
|View full text |Cite
|
Sign up to set email alerts
|

Proper Utilization of Adequatly Iodized Salt at House Hold Level and Associated Factores in Asella Town Arsi Zone Ethiopia: A Community based Cross Sectional Study

Abstract: Back ground: In Ethiopia the proportion of house holds with adequately iodized salt and knowledge and practices on proper utilization of adequatly iodized salt was low to achieve the target for elimination of iodine deficiency disorder. The objectives of this study was to assess the proper utilization of adequately iodized salt and associated factors at house hold level in Asella town, Arsi Zone Ethiopia in 2015. Methods and material:A Cross-sectional study design with multi stage sampling technique was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
4
3
Order By: Relevance
“…The finding of this study revealed that adequacy of iodized salt was much higher than reports from rural community of Maychew (33%) [21], West Ethiopia (8.7%) [22] and Gondar town, Ethiopia (28.9%) [23] and Asella Town, Ethiopia (62.9%) [24]; and similar result was observed from urban area of Sidama Zone, Ethiopia (65%) [25]. Even though there are many variation and strategies across countries, the finding of the study was also higher as compared to findings from other low income contries [13, 26]. In contrast to the above finding, adequacy of iodized salt in the study was lower than findings from EasternNepal (82.6%) [27] and Telangana, India (79%) [3].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The finding of this study revealed that adequacy of iodized salt was much higher than reports from rural community of Maychew (33%) [21], West Ethiopia (8.7%) [22] and Gondar town, Ethiopia (28.9%) [23] and Asella Town, Ethiopia (62.9%) [24]; and similar result was observed from urban area of Sidama Zone, Ethiopia (65%) [25]. Even though there are many variation and strategies across countries, the finding of the study was also higher as compared to findings from other low income contries [13, 26]. In contrast to the above finding, adequacy of iodized salt in the study was lower than findings from EasternNepal (82.6%) [27] and Telangana, India (79%) [3].…”
Section: Discussionsupporting
confidence: 62%
“…Many studies agreed that iodized salt was not accessible for most of the poor society in the world. Reports from Asella town [24], Sidama Zone [25] and rural India [26] postulated that the better socio-economic status, the more adequately iodized salt used and agreed that packed iodized salt is not affordable for the poor.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 48.5% were confirmed with ≥15 ppm iodine content in their daily salt which self-reported as they always used adequate iodized salt utilization. Which is considerably lower than the WHO recommendation levels to be 90%, 24 Pradesh Indian 48%, 25 Mayhew district (59.7%), 26 Dessie town 68.8%, 20 Asella town 76.8% in 2016, 27 Goba town 57.2%, 28 Dega Damot 88.8% 29 but higher than previous finding in 33.2% in Gondar, 30 33.5% in Addis Ababa, 16 and 25.7% in Ziway. 26 This might be due to the difference in whether there was a problem in the identification of iodized salt during purchasing from the whole sellers, shops, and others where iodized salt was sold and the lower global and regional levels.…”
Section: Discussioncontrasting
confidence: 58%
“…The World Health Organization’s goal of eradicating iodine deficiency illnesses (≥90%) is substantially exceeded by this finding ( 1 ). According to the findings of this study, the proportion of households with adequate iodized salt is less than in earlier studies from Combolcha (68.8%) ( 25 ), Assella (62.5%) ( 26 ), and Dera (57.4%) ( 27 ), Oromia Regional State, South East Ethiopia (61.1%) ( 28 ), Southeast Ethiopia (56.6%) ( 28 ), Kolfe Keraniyo, Addis Ababa (95.5%) ( 29 ), Sidama Zone (65%) ( 30 ), China (89%) ( 31 ), Ghana (75.6%) ( 32 ), and India (75%) ( 33 ). This may be a result of the market’s accessibility and availability of iodized salt, as well as laws, policies, and ongoing follow-up and monitoring of the use of iodized salt in various nations.…”
Section: Discussioncontrasting
confidence: 74%